Evidence Insufficient to Confirm the Value of Population Screening for Diabetes and Hypertension in Low- and Middle-Income Settings - Durao, Solange; Ajumobi, Oluwayemisi; Kredo, Tamara; Naude, Celeste; Levitt, Naomi S.; Steyn, Krisela; Bradshaw, Debbie; Young, Taryn (Health and Medical Publishing Group, 2015)
To assess the evidence from systematic reviews on the effect on morbidity and mortality of blanket screening for hypertension or diabetes mellitus compared with targeted, opportunistic or no screening, we searched for relevant systematic reviews and conducted duplicate study selection, data extraction and quality appraisal. Results were summarized narratively. We included two completed reviews of moderate quality and one ongoing Cochrane review. In one completed review, general health checks had no effect on total morbidity or mortality or on healthcare services compared with no health checks. In the other, intensive hypertension screening methods were ineffective in increasing screening uptake or detecting new cases compared with less intensive methods. Both reviews included studies in high-income settings. There is insufficient evidence from currently available systematic reviews to confirm a beneficial effect of blanket screening for hypertension and/or diabetes compared with other types of screening methods in low- and middle-income settings. Scarce resources are being mobilized to implement mass screening intervention for diabetes and hypertension without adequate evidence of its effects. A systematic review is needed to assess clinical effectiveness, cost-effectiveness and overall impact on the health system of screening strategies, especially in low- and middle-income settings such as exist in South Africa. Robust evaluation of these outcomes would then be necessary to inform secondary prevention strategies.